Pseudogout Associated Hip Pain in a Patient with HIV Infection - Benan M. Dala-Ali; Matthew Welck; Mary Anne Lloyd; Henry D. Atkinson (Case Reports in Medicine)
HIV infection is a global pandemic, currently affecting approximately 77,000 people in the UK and 33 million people around the world. The infection has widespread effects on the body and can involve the musculoskeletal system. It is therefore important that orthopaedic surgeons are aware of the condition and its sequelae. We present the case of a 46-year-old man with a 10-year history of HIV who presented with acute hip pain, difficulty weight-bearing, and constitutional symptoms. Following radiological, microbiological, and serological tests a diagnosis of pseudogout was established following microscopic analysis of the hip joint aspirate. The patient's symptoms resolved completely following the joint aspiration and NSAID therapy. Studies have shown a relationship between HIV infection and gout. The virus has also been linked to osteonecrosis, osteopenia, bone and joint tuberculosis, and septic arthritis from rare pathogens. However, it is difficult to fully ascertain whether these conditions are related to the HIV infection itself or the HAART (highly active antiretroviral therapy). There are no previously reported cases of HIV-infected patients with pseudogout. The case is discussed with reference to the literature.